Motivation to Learn English: Why Indonesian Adult Learners Join a Community of Interest - Nurhapsari Astriningsih; Concilianus Laos Mbato (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2019)
The importance of having a mastery of the English language has motivated language students to learn, not only in class, but also through other informal extra-curricular activities. One of these activities is gathering together in communities of interest. Motivation has been proven to have an impact on the success of learners in organizing their language-learning activities. Via Likert-scale questionnaires and semi-structured interviews, this study has examined motivation towards the study of English amongst members of a community of interest in Yogyakarta, Indonesia. The participants in this study were 85 English language club members, studying across a number of fields in several Yogyakarta universities. Six participants were then chosen for interview. On the basis of quantitative and qualitative analysis, these learners showed a high level of motivation in all aspects, with slight dominance for intrinsic and instrumental motivation. The research offered implications for further study.